Endolimax nana and urticaria - Stefano Veraldi; Luisa Angileri; Luisa Carlotta Rossi; Gianluca Nazzaro (Journal of Infection in Developing Countries)
Endolimax nana is a commensal protozoan of the colon. We report a case of chronic urticaria associated with E. nana in a 34-year-old Italian woman. The patient suffered from abdominal pain, diarrhoea and weight loss. The disease appeared after a trip to Vietnam. Laboratory examinations showed mild blood eosinophilia. Three coproparasitological examinations were positive for cysts of E. nana. The patient was successfully treated with two courses of metronidazole (2 g/day for 10 days each). No antihistamines were used. Three coproparasitological examinations, carried out at the end of the therapy, were negative. Follow up (six months) was negative. E. nana can be responsible for very rare cases of abdominal pain, diarrhoea, polyarthritis and urticaria.